Tunable morphology and band gap alteration of CuO-ZnO nanostructures based photocathode for solar photoelectrochemical cells - A Albadarin, Nusayba (Institute of Physics Publishing, 2020)
A homogeneous CuO-ZnO nanostructure with tunable morphology and optical band structure is successfully synthesized via a hydrothermal method under the different dopant mole ratios of Cu. The robust correlation between the crystallite size, surface morphology, optical band gap alteration of the synthesized CuO-ZnO and its performance in photoelectrochemical (PEC) activity are investigated and compared to the reference ZnO based photocathode. In this report, it is found that the morphology of hexagonal ZnO nanorod is changed to nanosheet and vertically align CuO-ZnO based nanograss after the Cu incorporation. This result is mainly due to the composition phase change after the excessive incorporation of Cu metal into ZnO lattice. Furthermore, the optical band gap of the sample also presented a bathochromic shifted after the Cu insertion. The measurements on PEC activity of CuO-ZnO nanostructure was performed under the irradiation of a 100 mWcm−2 Xenon light in 0.5M Na2SO4 electrolyte. Among the sample, 0 Zn:1 Cu exhibited a highest photocurrent density which is 5 fold as compared to its reference ZnO samples. This finding could be due to the highest surface active area and lowest optical energy band gap in the 0 Zn:1 Cu nanograss that eventually contributes to a high free electron density that facilitates the charge transport in the photoelectrochemical cells. This novel approach could provide an alternative to the future solar hydrogenation application.